Strengthening Legal Enforcement in the Indonesian Insurance Sector: Regulatory Gaps and Policy Reform Agenda - Hayamanysah, Didi; Suseno, Sigid; Gultom, Elisatris (PRAWO i WIĘŹ, 2025)
The purpose of this study is to assess the effectiveness of current insurance regulation in Indonesia and to propose legislative reforms to improve policyholder protection and prevent fraudulent practices within the industry. The research focuses on identifying regulatory weaknesses that allow fraud and mismanagement to persist, using the AJB Bumiputera 1912 case as a primary example. A legal-normative approach was adopted, analysing insurance-related legislation, court decisions and regulatory frameworks in comparison with those of other countries. Secondary data was collected from legal sources, reports from the Financial Services Authority (OJK) and the Financial Transaction Reports and Analysis Centre (PPATK), and existing literature on insurance fraud and regulatory oversight.